Strikes as Safety-Valve Institutions - Chermesh, Ran (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
The present study argues for the usefulness of searching for factors outside of the sub-system of industrial relations as partial causes of stike activity. It treats the industrial relations sub-system as an internal part of the overall social System, in which strikes are regarded as expressions of generalized social tension, i.e., as safety-valve institutions.